2017
DOI: 10.1111/1467-8551.12229
|View full text |Cite
|
Sign up to set email alerts
|

Reality or Illusion? The Efficacy of Non‐market Strategy in Institutional Risk Reduction

Abstract: Non‐market strategy researchers have postulated that political and social strategies reduce the exposure of firms to risk, but those arguments have received little empirical attention. In this paper, we integrate social capital and institutional theories to examine the efficacy of managerial political ties (MPTs) and corporate social responsibility (CSR) in institutional risk reduction. Using survey data from 179 firms in Ghana we find that, whereas CSR reduces institutional risk exposure, MPTs do not. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 160 publications
(238 reference statements)
2
71
0
Order By: Relevance
“…In contrast, the paper by Liedong, Mellahi and Rajwani (2017) in this special issue finds no evidence for complementarity. The authors found that CSR helps to lower perceptions of risk exposure but is ineffective when combined with managerial political ties (MPTs), thereby 'suggesting the existence of a form of "cannibalization" whereby MPTs erode the gains of CSR'.…”
Section: Cpa−csr Substitutionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast, the paper by Liedong, Mellahi and Rajwani (2017) in this special issue finds no evidence for complementarity. The authors found that CSR helps to lower perceptions of risk exposure but is ineffective when combined with managerial political ties (MPTs), thereby 'suggesting the existence of a form of "cannibalization" whereby MPTs erode the gains of CSR'.…”
Section: Cpa−csr Substitutionmentioning
confidence: 64%
“…The papers by Liedong, Mellahi and Rajwani (2017) and Ahammad, Tarba, Frynas and Scola (2017) provide some novel insights on the integration of social and political strategies and the integration of market and non-market strategies. But they have practical implications too.…”
Section: Contributions In This Special Issuementioning
confidence: 99%
“…For example, it can achieve favorable legislative decisions (Lord, ), generate higher market capitalization (Hillman, ), improve the firm value in stock markets (Goldman, Rocholl, & So, ), lead to enhanced financial performance (Shaffer, Quasney, & Grimm, ), and decrease business risk (Puck et al, ). Yet, there is limited work exploring the links between sociopolitical strategies and their influence on firm performance in EMs (e.g., Frynas & Stephens, ; Hadani & Coombes, ; Leidong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current lack of integration of political and social strategies research means that there is limited understanding of complementary or substitution effects between the political and social strategies (cf. Leidong, Rajwani, & Mellahi, 2017;Mellahi et al, 2016). In the context of EMs, extant literature has examined the different types of political and social strategies used by foreign companies in those markets, mainly focusing on the determinants of such strategies rather than on the outcomes (Hillman & Hitt, 1999;Hillman, Keim, & Schuler, 2004;Meznar & Nigh, 1995;Oliver & Holzinger, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation